Some Common Fixed Points Theorems of Four Weakly Compatible Mappings in Metric Spaces (Baghdad Science Journal, 2021)
In this paper, we proved coincidence points theorems for two pairs mappings which are defined on nonempty subset   in metric spaces by using condition (1.1). As application, we established a unique common fixed points theorems for these mappings by using the concept weakly compatible (R-weakly commuting) between these mappings.